Effect of Sn dopants on the optical and electrical properties of ZnO films - Aksoy, Seval; Caglar, Yasemin; Ilican, Saliha; Caglar, Mujdat (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The undoped and tin (Sn) doped ZnO films were deposited by a spray pyrolysis method onto the glass substrates. 0.2 M solution of zinc acetate in a mixture of ethanol and deionised water, in a volume proportion of 3 : 1, was employed. Dopant source was tin chloride. The atomic percentage of dopant in solution were Sn/Zn = 1%, 3% and 5%. The effect of tin doping on the optical and electrical properties of ZnO films was studied. The optical transmittance was about 76% in a visible range for Sn-doped ZnO films. The optical band gaps of the films were calculated. This suggests that the absorption edge shifts to the lower wavelengths with Sn dopant. Optical constants of the films were determined. These parameters changed with Sn dopant.
Optica Applicata, Vol. 40, 2010, nr 1, s. 7-14
Keywords: optyka; ZnO film; optical band gap; optical constant; figure of merit